2017
DOI: 10.29252/archhygsci.6.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals in Vegetables and Cereals- A Case Study of Indian Market-2016

Abstract: In 21st Century trace metals contamination in vegetables and cereals is a serious growing concern due to their accumulation, persistence and toxicity in nature (1-3). Vegetables and cereals are rich sources of carbohydrates, proteins, vitamins, minerals as well as trace elements and fibers and also have beneficial antioxidative effects (4-6). Eating of polluted vegetables and cereals may encounter human health. One item that should be considered for quality of food is heavy metal contamination. (7,8). Sudden i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Other vegetable sample were also found contaminated with arsenic, taro root (1.32 mg/kg), potato (1.203 mg/kg), jackfruit (1.20 mg/kg), onion (0.29 mg/kg), beans (0.08 mg/kg) and pumpkin (0.06 mg/kg). Lower level in spinach (0.23 µg/g), potato (0.19 µg/) and onion (0.21 µg/g) were reported in a study in Varanasi [48], in potato (<0.1) [50]; lower arsenic reported in spinach (0.016 µg/g), onion (0.023 µg/g), potato (0.025 µg/g), pumpkin (0.053 µg/g) and beans (0.080 µg/g) from Sindh, Pakistan [1]; in vegetables (0.47±0.54 mg/kg) in Kolkata [12]; another study conducted in Bangladesh showed high values in bean (0.31 mg/kg) and jackfruit (0.16 mg/kg) and lower levels in potato (0.27 mg/kg), mango (0.17 mg/kg) and similar concentration (0.29 mg/kg) in onion [21]; in jackfruit (0.007 mg/kg), mango (0.013 mg/kg), bean (0.018 mg/kg), onion (0.008 mg/kg) and potato (0.006 mg/kg) in Bangladesh [46] as compared to current study levels. A study from Vadodara reported higher arsenic levels as compared to this study in spinach (5.0 ppm), onion (5 ppm) and potato (5 ppm) [10].…”
Section: B Arsenicmentioning
confidence: 62%
See 2 more Smart Citations
“…Other vegetable sample were also found contaminated with arsenic, taro root (1.32 mg/kg), potato (1.203 mg/kg), jackfruit (1.20 mg/kg), onion (0.29 mg/kg), beans (0.08 mg/kg) and pumpkin (0.06 mg/kg). Lower level in spinach (0.23 µg/g), potato (0.19 µg/) and onion (0.21 µg/g) were reported in a study in Varanasi [48], in potato (<0.1) [50]; lower arsenic reported in spinach (0.016 µg/g), onion (0.023 µg/g), potato (0.025 µg/g), pumpkin (0.053 µg/g) and beans (0.080 µg/g) from Sindh, Pakistan [1]; in vegetables (0.47±0.54 mg/kg) in Kolkata [12]; another study conducted in Bangladesh showed high values in bean (0.31 mg/kg) and jackfruit (0.16 mg/kg) and lower levels in potato (0.27 mg/kg), mango (0.17 mg/kg) and similar concentration (0.29 mg/kg) in onion [21]; in jackfruit (0.007 mg/kg), mango (0.013 mg/kg), bean (0.018 mg/kg), onion (0.008 mg/kg) and potato (0.006 mg/kg) in Bangladesh [46] as compared to current study levels. A study from Vadodara reported higher arsenic levels as compared to this study in spinach (5.0 ppm), onion (5 ppm) and potato (5 ppm) [10].…”
Section: B Arsenicmentioning
confidence: 62%
“…Highest Cd was found in leafy vegetable samples of taro root leaves (1.26 mg/kg) and spinach (1.18 mg/kg) followed by jackfruit (0.49 mg/kg), taro root (0.35 mg/kg), mango (0.28 mg/kg), beans (0.27 mg/kg), pears (0.25 mg/kg), blackberry (0.23 mg/kg), pumpkin (0.22 mg/kg) and onion (0.22 mg/kg). A higher level of Cd was reported in spinach (14.58 mg/kg) [17] in West Bengal, (15.24 mg/kg) in spinach from Allahabad [52]; in pears (3.85 and 7.58 µg/kg) and mangoes (2.14 and 16.9 µg/g) from two market areas of Bangalore city [28]; high Cd level in spinach (4.1 µg/g) and potato (2.50 µg/g) while a slightly high level in onion (0.20 µg/g), (1.96 mg/kg) in spinach from market site [47], another study reported high Cd concentration in spinach (1.60 ppm), potato (1.63 ppm) and onion (1.65 ppm) in Vadodara [10]; similarly from study in Varanasi showed slightly high values in onion (0.44 µg/g) and lower in spinach (0.94 µg/g) by [48] as compared to present study; high Cd values in (1.33 mg/kg) and (0.75 mg/kg). Other research reported lower value in spinach (0.37µg/g) and high value in beans (0.93µg/g) but Cd not detected in pumpkin [39].…”
Section: Cadmiummentioning
confidence: 78%
See 1 more Smart Citation
“…They provide us minerals, vitamins, essential amino acids and fibers. 1 Cereals have been the main component of the human diet since primitive times because of their large scale cultivation, blend flavor and a wide variety. 2 Cereals serve as a reliable source of energy and minerals to human beings as they are rich in carbohydrates, trace elements, vitamins and protein.…”
Section: Introductionmentioning
confidence: 99%